Flow Injection Determination of Thymol in Pharmaceutical Samples Via Oxidative Coupling Reaction with 2,4- Dinitrophenylhydrazine - Al-Abachi, Mouayed Q; Hadi, Hind; Fadhil, Ghadah (Al-Nahrain Journal of Science, 2018)
A fast and sensitive flow injection analysis (FIA) method for the quantitative determination of thymol (THY) in raw and pharmaceutical formulations have been proposed. The method is based on coupling reaction between THY and 2,4-dinitrophenylhydrazine in alkaline medium with presence of potassium periodate to form an intense violet water-soluble dye that is stable and has a maximum absorption at 570 nm. A graph of absorbance versus concentration indicates that Beer’s law is obeyed over the concentration range of 10-150 μg.mL-1 of THY, with detection limit of 5 μg.mL-1and sample throughputs of 60h-1. The proposed method was successfully applied to the determination of THY in mouth wash preparations.